Using tam to study the user acceptance of it in the yemeni public sector (Ministry of Social Affairs and Labour-Yemen) - Saeed Wahdain, Esmat Abdulmajid (2014)
Although IT offers promising improvements in public sector efficiency, there is a consensus that these cannot be realized until IT tools become widely spread and used. This study aims to improve the utilization of IT in the context of the Yemeni public sector by identifying the factors that influence IT user’s acceptance. The Research proposes a model based on the Technology Acceptance Model with some added factors that are believed to have a significant influence in the context being studied, such as: organizational culture and individual factors as external factors, perceived personal benefit, and gender as a moderator to the relationships between organizational culture and both perceived usefulness and perceived personal benefit. To test the model and the proposed hypotheses, quantitative method was used. A questionnaire was prepared and validated by five experts, and then distributed and answered by 139 employees of the ministry of Social Affairs and Labour (MoSAL) in Hadhramout- Yemen, who use IT in their jobs. The SmartPLS software was used to test measurement model, and to assess the structural model and test the proposed hypotheses. The results revealed the significance of the proposed factors, organizational cultural was found to be very influential on perceived usefulness and perceived personal benefit, and perceived usefulness, in turn, was very important determinant of attitude, and consequently, on the behavioural intention of employees towards using IT, the gender impact was also proven statistically, however, the individual factors was found to have no significant influence on the perceived personal benefit, as the model suggested. The study is expected to have significant impact on the study domain, public sector in Yemen, by enriching the managerial knowledge about the importance of the factors investigated in this study. More importantly, the study will enrich the body of literature on technology acceptance by introducing a case study that has not been previously covered, namely, a public sector organization in a growing country with special cultural and social conditions.